2013
DOI: 10.1111/j.1600-0587.2013.00030.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic diversity of geometrid moths decreases with elevation in the tropical Andes

Abstract: Species diversity of geometrid moths (Lepidoptera, Geometridae) has previously been shown to be extremely and constantly high along a continuously forested elevational gradient in the Andes of southern Ecuador. We analysed samples taken from 32 sites between 1999 and 2011 in northern Podocarpus National Park and adjacent areas from 1020 to 2916 m a.s.l. We conjecture that high elevation habitats were historically mostly colonised by species from lower elevations, and that environmental filtering (e.g. through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 57 publications
4
41
0
Order By: Relevance
“…We hypothesize that colonization in South America has usually started in the large lowlands and that the colonization of mountains was impeded by environmental filtering, such as the availability of certain host plants that are not present at higher elevations in the Andes or other Neotropical mountain ranges, as suggested, for example, for Neotropical geometrid moths (Brehm et al . ). Some genera of arctiines also occur at high elevations or are even restricted to high‐elevation habitats.…”
Section: Discussionmentioning
confidence: 97%
“…We hypothesize that colonization in South America has usually started in the large lowlands and that the colonization of mountains was impeded by environmental filtering, such as the availability of certain host plants that are not present at higher elevations in the Andes or other Neotropical mountain ranges, as suggested, for example, for Neotropical geometrid moths (Brehm et al . ). Some genera of arctiines also occur at high elevations or are even restricted to high‐elevation habitats.…”
Section: Discussionmentioning
confidence: 97%
“…For example, in an Ecuadorian study, within the Geometridae, moths of the subfamily Larentiinae were on average smaller than moths of the subfamily Ennominae, and proportions of subfamilies in the local fauna changed along an elevational gradient (Brehm and Fiedler 2003, 2004, Fiedler et al 2008, Brehm et al 2013. For example, in an Ecuadorian study, within the Geometridae, moths of the subfamily Larentiinae were on average smaller than moths of the subfamily Ennominae, and proportions of subfamilies in the local fauna changed along an elevational gradient (Brehm and Fiedler 2003, 2004, Fiedler et al 2008, Brehm et al 2013.…”
Section: Discussionmentioning
confidence: 99%
“…The species loss pattern can be related to physiological limitations of species ). Using phylogenetic information, Brehm et al (2013) showed that Geometrid moth assemblages at higher elevations of Andean mountains are phylogenetically clustered, indicating the loss of species richness due to environmental filtering at upslope sites. As this species loss did not increase linearly with elevation, it cannot be linked to available area, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have pointed out the importance of a wide variety of factors on the generation of biodiversity such as historical geology, specialization and topographical variation (e.g. Brehm et al 2013;Pyrcz et al 2013). Yet both types of studies have been conducted mostly in tropical regions and cannot simply be generalized to the temperate BH regions.…”
Section: Introductionmentioning
confidence: 98%